Characterization of the attributes impacting industrial adoption of tree tomato fruit varieties in Kenya - Isaac M. Maitha; Michael W. Okoth; Lucy G. Njue; Duncan O. Mbuge (Cogent Food & Agriculture)
Tree tomato (Cyphomandra betacea), is a nutrient-dense fruit but the physicochemical properties differ depending on the origin and cultivar. The study aimed at characterizing attributes impacting value addition and industrial adoption of tree tomato fruits varieties in Kenya. The red and yellow tree tomato fruit varieties were procured from Marigiti market in Nairobi, Kenya which is the main aggregation center and samples were randomly selected for characterization. Subjective color assessment was used to sort the fruits before randomly selecting samples for physicochemical characterization. The fruits had uniform, consistent geometric features which make them suitable for high-speed automated processes, suitable for selecting preparative unit operations to yield good quality end products. The color properties contribute to better understanding of the colorimetric aspects of tree tomatoes, which are important in selecting the best varieties of known processing performance, and best fruit pretreatments to help retain the natural color, value and quality of end products. The Chemical characterization results are important in designing and controlling the process to get high quality, nutritious and functional end products. The Kenyan red, compared to the yellow tree tomato had more promising functional properties, hence highly recommended as a valuable raw material for innovative food products.